Prevalence of and factors associated with inappropriate Clostridioides difficile testing in a teaching hospital in Korea - Hee Bum Jo; Sin Young Ham; Jongtak Jung; Song Mi Moon; Nak-Hyun Kim; Kyoung-Ho Song; Jeong Su Park; Kyoung Un Park; Eu Suk Kim; Hong Bin Kim (Antimicrobial Resistance and Infection Control, 2022)
Abstract Background Given the increasing incidence of Clostridioides difficile infections in Korea, there has been an increase in inappropriate testing for C. difficile, which has rendered overdiagnosis of asymptomatic colonisers common. We aimed to investigate the appropriateness of C. difficile testing and the related factors. Methods We retrospectively reviewed the medical records of patients who were admitted to a 1300-bed tertiary-care teaching hospital in Korea and were tested for C. difficile infection from September 2019 to November 2019. We performed logistic regression analysis to investigate factors related to inappropriate testing. Further, a survey was conducted on physicians to assess the knowledge and ordering patterns of C. difficile testing. Results We included 715 tests from 520 patients in the analysis. Testing was classified as hospital-onset and community-onset and subclassified as appropriate and inappropriate following an algorithmic method. Among the 715 tests, 576 (80.6%) and 139 (19.6%) tests were classified as hospital-onset and community-onset, respectively. Among the hospital-onset tests, 297 (52%) were considered inappropriate. The risk of inappropriate testing increased when C. difficile tests were conducted in the emergency room (OR 24.96; 95% CI 3.12–199.98) but decreased in intensive care units (OR 0.36, 95% CI 0.19–0.67). The survey was conducted on 61 physicians. Internal medicine physicians had significantly higher scores than non-internal medicine physicians (7.1 vs. 5.7, p = 0.001). The most frequently ordered combination of tests was toxin + glutamate dehydrogenase (47.5%), which was consistent with the ordered tests. Conclusion Almost half of the C. difficile tests were performed inappropriately. The patient being located in the emergency room and intensive care unit increased and decreased the risk of inappropriate testing, respectively. In a questionnaire survey, we showed that internal medicine physicians were more knowledgeable about C. difficile testing than non-internal medicine physicians. There is a need to implement the diagnostic stewardship for C. difficile, especially through educational interventions for emergency room and non-internal medicine physicians.